2021
DOI: 10.1177/23998083211019756
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of elderly daily travel behaviour in Tianjin using a space–time cube

Abstract: The elderly may have unique, daily travel behaviour characteristics compared to other age groups, associated with age and physical ability. Defining these characteristics can inform urban infrastructure construction and planning. In this study, 20 elders aged between 60 and 70 years, living in the city centre of Tianjin, were selected to complete the survey. A total of 2232 hours of participant travel behaviour were collected via GPS equipment from July to August 2019. Data were used to create a space–time cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…According to relevant research results ( Jaeger and Bowman, 2005 ; Wen et al, 2014 ; Qianwen et al, 2016 ; Sen et al, 2021 ), seven types of urban spaces—residential communities, vegetable markets, bus stops, parks, shopping streets, hospitals, and urban functional departments—have high travel frequency. Based on these urban spaces, a total of 24 scenes were selected in this study; all scenes were outdoors.…”
Section: Methodsmentioning
confidence: 99%
“…According to relevant research results ( Jaeger and Bowman, 2005 ; Wen et al, 2014 ; Qianwen et al, 2016 ; Sen et al, 2021 ), seven types of urban spaces—residential communities, vegetable markets, bus stops, parks, shopping streets, hospitals, and urban functional departments—have high travel frequency. Based on these urban spaces, a total of 24 scenes were selected in this study; all scenes were outdoors.…”
Section: Methodsmentioning
confidence: 99%
“…Yanagihara [17] found that older adults with good physical health were more likely to drive to their destinations. Zhang et al [18] found that older adults' travel time was mainly related to the purpose of travel, with bicycles used for shorter travel times rather than walking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Comfortable environments promote active travel among older adults. Travel time is an important indicator of perception and travel behavior [18,23]. It can also measure the intensity of physical activity in older adults [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study results show that public service facilities have a strong impact on connectivity between different places. Statistics and analysis results show there are mainly 6 kinds of travel behaviors of the elderly, which include visiting and shopping [35].…”
Section: Literature Reviewmentioning
confidence: 99%